2009
DOI: 10.1089/end.2009.0388
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Locally Advanced (T3 or Greater) Prostate Cancer in Men Undergoing Robot-Assisted Laparoscopic Prostatectomy

Abstract: RALP is a feasible approach to patients with pathologically advanced PCa as 71% were without evidence of disease at 13 months postoperatively. PSM rate (20%) is comparable to previously reported open PSM rates (24-66%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…10 The increasing availability of robotic technology to urologists has expanded the role and indications for RARP, including recent reports of this approach in a high-risk setting. [11][12][13][14][15] We evaluated short-term functional and oncologic outcomes in patients with high-risk CaP undergoing RARP at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…10 The increasing availability of robotic technology to urologists has expanded the role and indications for RARP, including recent reports of this approach in a high-risk setting. [11][12][13][14][15] We evaluated short-term functional and oncologic outcomes in patients with high-risk CaP undergoing RARP at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…Small median lobes or flat trigones were considered 'normal' [7]. A bilateral nerve-sparing technique was performed unless an extended resection was indicated for Gleason scores of 8-10 with palpable disease or greater than 20% volume on that side [8]. The first 61 RALRPs were performed using a standard Van Velthoven technique for the vesico-urethral anastomosis [9].…”
Section: Intra-operative Data and Surgical Techniquementioning
confidence: 99%
“…Reports of early experiences with RALP have not had a major impact and studies in over 1000 cases in a single institution have already been reported. 1,2 However, robotic surgery has not been sufficiently adopted in Asia yet. The number of da Vinci systems in service around the world at present exceeds 1000, but 70-80% of those are in the USA and the majority of the rest are in Europe.…”
Section: Editorial Comment From Dr Kadono To Robotic-assisted Laparosmentioning
confidence: 99%
“…These numbers are certainly higher than those reported in manuscripts that solely focus on the role of RALP in patients with pT3 disease, albeit with more experienced surgeons. 2 The authors make the conclusion that 100 cases are not enough to adequately manage the surgical margins in patients with locally advanced disease.…”
mentioning
confidence: 99%